Dental anxiety reduction and dental attendance after treatment in a dental fear clinic: a follow-up study - Aartman IHA, de Jongh A, Makkes PC, Hoogstraten J (Blackwell Synergy, 2000)
The aim of the present study was to assess treatment outcome in terms of dental anxiety reduction at a post-treatment assessment and dental anxiety reduction and dental attendance one year later. Furthermore, it was determined to what extent psychopathological characteristics were related to treatment outcome.